NEO-KAJANG: SEBUAH TIPOLOGI BARU PEMUKIMAN EKOLOGIS BAGI KOMUNITAS SUKU LAUT - Octaviany Octaviany; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2021)
The development of the city today is not all in a positive direction. urban growth that is too fast and unplanned, it can cause changes to lifestyle, knowledge, locality, identity, etc. The Sea Nomad is a community that is known to live on a canoe called a kajang. However, since the 1990s, the Sea Nomad has been placed in a marginal position and also does not know civilization and modernity, so it is categorized as an isolated Nomad. Therefore, the Sea Nomad became a target in the government's agenda, namely by limiting their access to the sea and building settlements for them. This forces the Sea Nomad to live a different lifestyle from the one they used to live, bringing themselves to a new awareness of